HYBRID TSR-PSR PROTOCOL BASED FULL-DUPLEX ENERGY HARVESTING OVER RAYLEIGH FADING CHANNEL: SYSTEM PERFORMANCE ANALYSIS - Tran Tin, Phu; Tran, Minh; Nguyen, Tan N.; Nguyen, Thanh-Long (Institute of Advanced Engineering and Science, 2020)
Cooperative communication has been recently proposed in wireless communication systems for exploring the inherent spatial diversity in relay channels. In this work, we investigate the system performance of the energy harvesting full-duplex (FD) decode-and-forward (DF) hybrid TSR-PSR (TPSR) protocol relaying network. In the selection scheme, the best user selection protocol is proposed and investigated. Mainly we derive the closed-form expression for the outage probability, system throughput and the symbol error rate (SER) of the system. Numerical results are also presented by the Monte Carlo simulation to validate the theoretical analysis in connection with the all possible parameters in the comparison between TSPR, TSR and PSR cases. The research results show that TPSR case is better than the others in term of outage probability and SER.